Phase 1 Study Evaluating the Association of the Cyclin-Dependent Kinase 4/6 Inhibitor Ribociclib and Cetuximab in Recurrent/Metastatic p16-Negative Squamous Cell Carcinoma of the Head and Neck - Seront, Emmanuel; Schmitz, Sandra; Papier, Matthias; van Maanen, Aline; Henry, Stéphanie; Lonchay, Christophe; Rottey, Sylvie; van Caloen, Gabrielle; Machiels, Jean-Pascal (Frontiers in Oncology, 2019)
Background The majority of human papillomavirus (HPV)-negative squamous cell carcinoma of the head and neck (SCCHN) present upregulation of the epidermal growth factor receptor and frequent alterations in the cyclin D1-cyclin dependent kinase 4/6 (CDK 4/6)-retinoblastoma protein (pRb) pathway, resulting in cell cycle progression and tumor proliferation. This study investigated the combination of ribociclib, an orally highly selective inhibitor of CDK 4/6, and cetuximab in recurrent and/or metastatic (R/M) SCCHN. Methods A phase I trial using a 3+3 design was performed to determine the dose limiting toxicity (DLT) and maximum tolerated dose (MTD) of ribociclib with standard dose of weekly cetuximab in HPV-negative patients with R/M SCCHN. Ribociclib was administered orally (3 weeks on/1 week off) at dose level 1 of 400 mg daily and dose level 2 of 600 mg daily. The MTD of ribocilib was then further evaluated in an expansion cohort. Results Ten patients were enrolled in the escalation trial. No DLTs were observed at dose level 1 (n=3); at dose level 2, one patient was replaced due to rapid disease progression, and one patient out of six evaluable patients experienced a DLT (grade 4 thrombocytopenia > 7 days). Ribociclib 600 mg daily was thus determined to be the MTD. Eleven additional patients were enrolled in the expansion cohort. Diarrhea (52%), rash (52%), fatigue (43%), nausea (33%), and mucositis (28%) were the most frequent grade 1 - 2 adverse events (AE). Neutropenia was the most frequent grade 3 - 4 AE (20%). Median progression-free survival (PFS) was 3.5 months (range 0.4 - 17.3 months) and median overall survival (OS) was 8.3 months (range 0.4 - 24.1 months). Among the 19 radiologically evaluable patients, two (10.5%) achieved a partial response and 11 (58%) had stable disease. Conclusions The MTD of ribociclib is 600 mg daily when administered in combination with standard dose cetuximab for three weeks on and one week off. This combination was safe and showed efficacy. Further clinical trials should be conducted to evaluate the antitumor effects of this combination.